Globalización, Geografía política y Fronteras - Boisier, Sergio (Anales de Geografía de la Universidad Complutense, 2003)
Territory and geography in globalization. Multidimensional assessment. Geography and globalization frontiers: from past political geography’s strictness to future virtual political geography’s flexibility. Land planning and trans-frontier integration in Latin America: beyond the Nation-State.